Autoimmune thyroid disease in systemic lupus erythematosus. Issue 1 (1st January 2002) - Pyne, D; Isenberg, D A
Abstract : Background: The reported prevalence of autoimmune thyroid disease (3.9–24%) and antithyroid antibodies (11–51%) in SLE varies considerably. Early reports were mainly based on short term studies of small cohorts. Objective: To report the prevalence of autoimmune thyroid disease and thyroid antibodies in 300 patients with SLE, followed up at our centre between 1978 and 2000, by a retrospective analysis of case notes. Results: The prevalence (5.7%) of hypothyroidism in our cohort was higher than in the normal population (1%), while that of hyperthyroidism (1.7%) was not significantly different. Overall 42/300 (14%) of our cohort had thyroid antibodies, rising to 15/22 (68%) in the subgroup who also had thyroid disease (p<0.001). Both antimicrosomal and antithyroglobulin antibodies were detected. The antibodies were found in equally high frequency in the hyperthyroid subgroup (80% patients), whereas in the hypothyroid subgroup antimicrosomal antibodies were more frequent than antithyroglobulin antibodies (64% v 41%). There was no significant difference in the frequency with which antimicrosomal or antithyroglobulin antibodies were detected between the hyperthyroid and hypothyroid subgroups (p>0.2). Conclusion: Our patients with SLE had a prevalence of hypothyroidism, but not hyperthyroidism, greater than that of the normal population. The presence of either condition was associated with a higher frequency of both antimicrosomal and antithyroglobulin antibodies.